2003
DOI: 10.1111/j.1749-7345.2003.tb00087.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Experimental and Practical Diets for Bluegill Lepomis macrochirus and Hybrid Bluegill L. cyanellus × L. macrochirus

Abstract: Two experiments were conducted to identify appropriate experimental and practical diets for bluegill Lepomis macrochirus and hybrid bluegill L. cyanellus × L. macrochirus reared in aquaria. In the first study, four experimental diets and five commercial diets were evaluated in juvenile hybrid bluegill initially weighing 4.8 g/fish. The experimental diets contained casein (CAS), casein + gelatin (CAWGEL), casein + L‐arginine‐HCI (CAS/ARG), or casein + gelatin + crystalline amino acids (CAS/AA) as sources of cru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…Determinations of AGR for group‐reared bluegills from other nutrition studies have shown similar values: 0.1 g day −1 AGR for 6 g bluegill reared for 75 days (Hoagland et al. 2003), and 0.14–0.23 g day −1 of AGR for 8–14 g bluegill reared for 56 days (Twibell et al. 2003).…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…Determinations of AGR for group‐reared bluegills from other nutrition studies have shown similar values: 0.1 g day −1 AGR for 6 g bluegill reared for 75 days (Hoagland et al. 2003), and 0.14–0.23 g day −1 of AGR for 8–14 g bluegill reared for 56 days (Twibell et al. 2003).…”
Section: Discussionmentioning
confidence: 72%
“…Bluegills are often fed high‐protein trout diets and were reported to perform better on such diets than on catfish diets (Twibell et al. 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that some hybrids have similar or different dietary protein and lipid requirements compared with their parents (Brecka et al, 1995;Twibell et al, 2003). Moreover, there are some suggestions that the hybrids showed heterosis in growth, survival and disease tolerance, distinguishable from their parent species (Logan, 1968;Blanc and Chevassus, 1982;Tuncer et al, 1990;Brecka et al, 1995;Moreau and Pauly, 1999;Harel and Place, 2003).…”
Section: Measurements and Assaysmentioning
confidence: 99%
“…Although the feeding of Bluegills can increase their size and condition (Schmittou 1969;Berger 1982;Murnyak et al 1984;Hoagland et al 2003;Twibell et al 2003), the effects of supplemental feeding on their reproductive rates is unknown. Mature female Bluegills in unfertilized ponds had lower gonad weights than mature females in fertilized ponds, suggesting preferential allocation of energy to somatic tissue when food is scarce (Aday et al 2006).…”
mentioning
confidence: 99%